2020
DOI: 10.3390/su12104089
|View full text |Cite
|
Sign up to set email alerts
|

Management Strategies for Wood Fuel Harvesting—Trade-Offs with Biodiversity and Forest Ecosystem Services

Abstract: Bioenergy is expected to contribute to mitigating climate change. One major source for bioenergy is woody biomass from forests, including logging residues, stumps, and whole trees from young dense stands. However, at increased extraction rates of woody biomass, the forest ecosystem, its biodiversity, and its ability to contribute to fundamental ecosystem services will be affected. We used simulation and optimization techniques to assess the impact of different management strategies on the supply of bioenergy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 41 publications
0
17
0
1
Order By: Relevance
“…Aherne et al [7] found that only harvesting of aboveground wood biomass, i.e., crowns and branches, would have an indifferent effect on the environment and would not deplete the cationic base resources of the soil in the long term. On the other hand, Eggers et al [8] have pointed out that the development of the innovative and cost-effective management systems for harvesting biomass from the young stands can provide the possibility of supplying a significant amount of the bioenergy while preserving the biodiversity or the ecosystem value.…”
Section: Introductionmentioning
confidence: 99%
“…Aherne et al [7] found that only harvesting of aboveground wood biomass, i.e., crowns and branches, would have an indifferent effect on the environment and would not deplete the cationic base resources of the soil in the long term. On the other hand, Eggers et al [8] have pointed out that the development of the innovative and cost-effective management systems for harvesting biomass from the young stands can provide the possibility of supplying a significant amount of the bioenergy while preserving the biodiversity or the ecosystem value.…”
Section: Introductionmentioning
confidence: 99%
“…For example, removal of hardwood trees and management of understory vegetation is key for restoring the longleaf pine ecosystem across its former range and maintaining open canopy conditions in other pine forest types [72,73]. While there are concerns about the effects of an increase in pellet exports on biodiversity, e.g., [21,40,74,75], a framework has been developed to identify mitigation practices that can help offset the potential impacts on species of concern from logging, thinning, and dead wood removal [76]. The framework, designed to help users systematically examine and address effects of management actions on life-history conditions of species of concern, was applied to the case of an endemic, keystone species in the SE US, the gopher tortoise (Gopherus polyphemus).…”
Section: Sdgs Relevant To Production Of Woody Pellets In the Se Usmentioning
confidence: 99%
“…Woody biomass for bioenergy is promoted to help mitigate climate change through displacement of fossil fuels and by increasing the resilience of forest ecosystems as carbon sinks through better management of natural resources [21,22]. However, bioenergy's climate mitigation potential, as well as effects on other SDGs, depends, in part, on local conditions [23], as well as on the scale and intensity of production for different types of feedstock and their supply chains [24].…”
Section: Introductionmentioning
confidence: 99%
“…Em 2017, o Jornal Washington Post (2017 publicou uma pesquisa aplicada, em 2013, cujo resultado apontou que seria necessário 1,7 planeta Terra para tornar o modelo de produção e consumo contemporâneo sustentável; ou seja, o ritmo do consumo da sociedade ao longo do Século XX foi maior que o tempo necessário para a recomposição da biodiversidade. Eggers et al, (2020) advertem que, ao explorar os recursos naturais, em especial, os bioprodutos, faz-se necessário atentar para as questões de sustentabilidade (ELKINGTON, 2001;SACHS, 2002, VEIGA, 2011 assim como para o risco de perda de biodiversidade, de serviços ecossistêmicos e impactos negativos sobre o solo e o ciclo hídrico (DÍAZ et al, 2019;ONU, 2021).…”
Section: Introductionunclassified